(untitled) (Medical Forum Monthly, 2023)
Objective: The present study aimed to assess the role of lung ultrasound for the diagnosis of neonatal respiratory disorders. Study Design: Prospective cross-sectional study Place and Duration of Study: This study was conducted at the Intensive Care Unit (NICU) of CMH, Lahore from July 2021 to December 2022. Materials and Methods: Neonates of gestational age ≥28 weeks with respiratory distress syndrome were enrolled. Chest X-rays (CXR) and Lung Ultrasound (LUS) were performed during the admission and repeated before or after 7 days depending on the need for examination. Different etiologies associated with neonatal respiratory distress such as respiratory distress syndrome (RDS), pleural effusion (PE), congenital diaphragmatic hernia (CDH), transient tachypnea of the newborn (TTN), pulmonary interstitial emphysema (PIE), pulmonary atelectasis (PA), meconium aspiration syndrome (MAS), and pneumothorax (PTX) were interpreted based on chest X-rays findings. Descriptive statistics were done using SPSS version 27. Results: Of the total 96 neonates, there were 51 (53.1%) male and 45 (46.9%) female neonates. Out of total neonates, the incidence of full-term, late preterm neonates (34-36 gestational weeks), and preterm (<34 gestational weeks) were 50 (52.1%), 22 (22.9%), and 24 (25%) respectively. About 88 (91.7%) neonates were delivered through cesarean section (CS) mode of delivery. The mean gestational age and birth weight of neonates was 36.8±2.94 weeks and 2480.9±748.67 grams respectively. Invasive ventilation, non-invasive ventilation, and surfactant therapy were different respiratory support used in 38 (39.6%), 16 (16.7%), and 28 (29.2%) respectively. Sensitivity and specificity of lung US diagnosed neonates for pneumonia, pneumothorax, respiratory distress syndrome, pulmonary atelectasis, and meconium aspiration syndrome 96.4/100%, 89.5/97.9%, 93.7/100%, 100/98.9%, and 91.8/100% respectively. Conclusion: The present study concluded that Lung Ultrasound (LUS) is a safe, reliable, and an alternate modality for the diagnosis of neonatal respiratory distress.